2009
DOI: 10.1002/ajh.21406
|View full text |Cite
|
Sign up to set email alerts
|

Role and prognostic significance of the Ki‐67 index in non‐Hodgkin's lymphoma

Abstract: Expression of Ki-67, a nuclear antigen protein present in all cycling cells, is used to determine the growth fraction of tumors. The aim of this study was to evaluate the role and prognostic significance of the Ki-67 proliferation index (PI) in non-Hodgkin's lymphoma. Ki-67 was assayed immunohistochemically in tissue samples of 319 patients with newly-diagnosed non-Hodgkin's lymphoma. In 268 patients, the Ki-67 PI was correlated with clinical course and outcome. The mean Ki-67 PI ranged from 26.6% in indolent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
106
2
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 25 publications
8
106
2
7
Order By: Relevance
“…Ki-67 is a valuable immunohistochemical marker to distinguish indolent from aggressive lymphomas, particularly in small needle biopsies where exact typing may not be possible (31). Several studies have demonstrated that high expression of Ki-67 is an adverse prognostic marker in systemic DLBCL (34)(35)(36). In the present study, it was also observed that Ki-67 expression is a significant prognostic parameter of poor prognosis in patients with PCNSL.…”
Section: Discussionsupporting
confidence: 63%
“…Ki-67 is a valuable immunohistochemical marker to distinguish indolent from aggressive lymphomas, particularly in small needle biopsies where exact typing may not be possible (31). Several studies have demonstrated that high expression of Ki-67 is an adverse prognostic marker in systemic DLBCL (34)(35)(36). In the present study, it was also observed that Ki-67 expression is a significant prognostic parameter of poor prognosis in patients with PCNSL.…”
Section: Discussionsupporting
confidence: 63%
“…1 Many previous studies have shown that an increased PI in certain types of B-cell NHLs is associated with a more aggressive disease course. [2][3][4][5][6][7][8] These studies have been performed on diagnostic lymph nodes and other non-marrow tissues. We have encountered many requests for PI determination of the lymphoma on marrow specimens in cases where the marrow was the only diagnostic specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Um marcador prognóstico bastante utilizado é o índice de proliferação celular, por meio da expressão de Ki-67, proteína nuclear que regula o ciclo celular e que pode ser reconhecida em todas as fases do ciclo mitótico, com exceção do G0, fase em que a célula não está se dividindo (FOURNEL-FLEURY et al, 1997b;GAMBICHLER et al, 2008;BROYDE et al, 2009;SOKOŁOWSKA et al, 2012). De acordo com Sokolowska et al (2012) podemos dividir a expressão de Ki-67 nos linfomas caninos de acordo com o número de células marcadas, como baixa (menos que 20%), média (de 21 a 50%) e alta (acima de 50%).…”
Section: Linfoma Cutâneo Caninounclassified
“…Tanto nos linfomas humanos quanto nos linfomas caninos, maior expressão de Ki-67 indica pior prognóstico (DUMMER et al, 1995;ABELE et al, 1997;FOURNEL-FLEURY et al, 1997b;BRYANT;BANKS;O'MALLEY, 2006;BROYDE et al, 2009;DUARTE, 2013;FLOOD-KNAPIK et al, 2013). Segundo alguns autores, alta expressão de Ki-67 é observada nas fases mais avançadas do linfoma cutâneo (DUMMER et al, 1995;GAMBICHLER et al, 2008;EDINGER et al, 2009 Apesar de ainda não haver protocolo estabelecido que controle o linfoma cutâneo a longo prazo, a quimioterapia com a lomustina parece ter maior índice de resposta e maior duração, quando comparada a outros protocolos de tratamento (RISBON et al, 2006;WILLIAMS et al, 2006;LAPRAIS;OLIVRY, 2017).…”
Section: Linfoma Cutâneo Caninounclassified
See 1 more Smart Citation